Marcadores clínicos e laboratoriais no diagnóstico e gravidade da infecção pelo vírus da dengue em menores de 15 anos no município de Goiânia - Abe, Adriana Helena de Matos (2011)
Introduction: Dengue is the most important emerging and reemerging disease in morbidity and mortality today. Among those affected. 2.5% die, and is increasing the number of deaths in children annually. In this group, in particular, early diagnosis is more difficult. Objectives: To identify clinical and laboratory markers for diagnosis and severity of dengue infection cases reported in the period 2001 to 2009 in children under 15 years old living in the city of Goiania, laboratory confirmed, describe sociodemographic data, tourniquet test and admissions performed. Methodology: Database Information System for disease surveillance of the City Health Department to Goiania was used to do a retrospective, descriptive, exploratory quantitative analysis, using the test of statistical significance t-student test, with significance level 5% and the final statistical analysis in SPSS 17.0. Results: In the period 2001 to 2009 were reported in the city of Goiania, 124,794 cases of dengue, of these 113,744 (91%), referring to residents of the capital. Among those under 15 years reported in this period, 22,278 were residents of Goiania. The tourniquet test was performed in 7428 (33.34%) of these children, 1,415 (6.36%) reported not having performed this test. 13,435 (60.30%), had this spot in blank and 1,222 (16.45%) were described as positive. Were documented 1043 hospitalizations of children in this period. Laboratory confirmation occurred in 10,756 cases. As a final classification was found 77% of Classic Dengue, Dengue with 7.4% of complications, 0.4% of Dengue Hemorrhagic Fever and 0.14% deaths, 15% were not classified. Among the laboratory markers found were registered 1,209 cases with IgM positive cases em108 DEN 1, DEN 2 in 14 cases and DEN 3 in 67 cases, Histopathology was cited positive in 4 cases, the hematocrit ranged from 21% to 81%, among the sociodemographic markers the race / ethnicity most marked in this population was white, children over 11 years were most affected, students complete basic education. The more clinical markers reported were fever, headache. myalgia, prostration; among hemorrhagic manifestations: petechiae and epistaxis; as signs of vascular leakage, ascites, pleural and pericardial effusion; warning sign most frequently reported were abdominal pain; the complications of gravity as myocarditis, shock and neurological manifestations have been reported among others. DEN 2 was the responsible for the highest number of severe symptoms. Conclusions: Were identified clinical markers for diagnosis and severity for Dengue in the period studied. The population of children showed severe signs of vascular leakage and neurological impairment. Despite the incompleteness of some data, it did not limit the study, which serves as the basis for a greater knowledge about dengue in children in this region.